2021
DOI: 10.3390/atmos12101335
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Cool Coatings as a Strategy to Improve Urban Equivalent Albedo at Various Latitudes

Abstract: This research study aimed to investigate the influences of angular-selective retro-reflective (AS-RR) and retro-reflective (RR) materials on the urban equivalent albedo (αeq). Full ray tracing solar analyses were conducted through the Monte Carlo-based numerical model validated in a previous work. Different geometry scenarios with different patterns of urban density were modelled. AS-RR and RR materials were alternately applied to the street and to the most irradiated façade. AS-RR materials were proposed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Recently, more research has been oriented toward the performance of RR materials for different angles of incidence that takes into account the irradiated surface geometry scenarios, the urban density, the microclimate, the durability, and the costs and benefits [84]. As a solution, an angular selective behavior was discussed to overcome the limitations of RR materials, especially in summer [85].…”
Section: Rr Materialsmentioning
confidence: 99%
“…Recently, more research has been oriented toward the performance of RR materials for different angles of incidence that takes into account the irradiated surface geometry scenarios, the urban density, the microclimate, the durability, and the costs and benefits [84]. As a solution, an angular selective behavior was discussed to overcome the limitations of RR materials, especially in summer [85].…”
Section: Rr Materialsmentioning
confidence: 99%
“…Furthermore, some coated materials can be nearly 1 • C cooler for concrete and about 5 • C cooler for asphalt pavements [28]. Manni and Nicolini [29] suggested that the use of cool coatings can be optimized to improve urban albedo.…”
Section: Introductionmentioning
confidence: 99%